(untitled) (ItalianoLinguadue, 2014)
Cantante, danzatrice, esperta di canti religiosi di tutto il mondo, Luz è figlia di quattro lingue diverse: spagnolo, olandese, inglese, italiano e ha letto poesie scritte in quelle lingue. Tema centrale, il legame fra l’individuo e la terra, sua madre, a cui tornare sempre. Terra da amare, rispettare, cantare. Earth - Mother Singer, dancer, expert on religious songs from around the world, Luz is the daughter of four different languages: Spanish, Dutch, English, Italian and she read poems written in these languages. The central theme is the link between the individual and the earth, the mother, to whom one always returns. Earth to love, to respect, to celebrate.